Students’ Learning Obstacle in Solving Statistical Reasoning Problems: Epistemological Study - Farid Gunadi; Tatang Herman; Sufyani Prabawanto (Gema Wiralodra, 2022)
In some cases, Statistical learning only applies some formulas without paying attention to developing students’ reasoning ability. So, statistical learning can cause missed conception to the students. A teacher should identify the students’ learning obstacles to achieve the learning objectives. This study aims to know the students’ learning obstacles in solving statistical reasoning problems from two aspects. The first is from the emic aspect; it is a student's viewpoint toward solving the statistical problem. The second is from the aspect of ethics; it is a student viewpoint toward the teacher’s teaching technique done in teaching statistics. This qualitative study employs the explorative case study with epistemology study to discuss the students’ learning obstacles. From the test result and interview of three participants, it is concluded that the students face some obstacles in statistical reasoning problem-solving. The teacher also still used conventional methods in teaching the students.